Catalytic asymmetric [3+2] cycloaddition of isomünchnones with methyleneindolinones. Issue 71 (13th August 2021) - Wang, Kaixuan; Xu, Chaoran; Hu, Xinyue; Zhou, Yuqiao; Lin, Lili; Feng, Xiaoming
Abstract : An enantioselective [3+2] cycloaddition of isomünchnones with methyleneindolinones catalyzed by asymmetric bimetallic Rh(ii )/Zn(ii ) relay catalysis is described. Abstract : An efficient enantioselective [3+2] cycloaddition of isomünchnones with methyleneindolinones that are generated by an in situ intramolecular addition of the carbonyl group to rhodium carbenes is realized with a chiral N, N ′-dioxide/Zn(ii ) complex as a Lewis acid. A series of chiral oxa-bridged 3-spiropiperidines are obtained in high yields with excellent dr and excellent ee values.